Respon Kognitif dan Afektif Siswa terhadap Media Pembelajaran Berbasis Android - Moh. Zulkifli Paputungan; Chaterina Puteri Doni; Fira Sutira Damulawan; Ceysi Yuliana Hasan (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2023)
This study analyzes students' cognitive and affective responses to Android-based learning media and its impact on learning outcomes. Using a descriptive method, the research involved 40 students. Data was collected through questionnaires measuring students' cognitive and affective responses, and multiple-choice tests administered before and after media use. Results show a significant improvement in student learning outcomes; all students achieved the minimum passing score (70) after using the media, with the highest score reaching 98. Students' cognitive responses to the media were highly positive, with percentage scores ranging from 75% to 82%, indicating the media's effectiveness in enhancing understanding and learning outcomes. Affective responses also showed positive results, with percentage scores between 81% and 84%, suggesting that students felt happy, motivated, and comfortable while learning. The study concludes that Android-based learning media is effective in improving academic achievement and creating an interactive and enjoyable learning environment for students. This approach can be an essential part of school learning strategies. The research highlights the potential of mobile technology in education, demonstrating its ability to engage students both cognitively and emotionally, thereby enhancing the overall learning experience and academic performance.